Passiflora brauliensis, a new species of Passiflora supersection Laurifoliae (Passifloraceae) from the volcanic forest of Costa Rica - Kuethe, J.r.; Rodríguez-Barboza, Gared; Álvarez-Alcázar, Leonardo (Phytotaxa, 2023)
A new species from Costa Rica is described following a closer analysis of the Passiflora nitida complex. Given that the actual true identification of Passiflora nitida typified from Venezuela but distributed throughout South America was rather poorly constrained, the new species presented here was long identified incorrectly as supposedly being a form of P. nitida, for it sharing several floral characteristics. Following intense revision of the source literature, supplemented by fieldwork across Central America, the Costa Rican accessions of “Passiflora nitida” appeared to be significantly different from its South American counterpart in several morphological and habitational characteristics. While it was found that true Passiflora nitida only inhabits non-volcanic terrains, Passiflora brauliensis sp. nov. presented in this paper attributes to be the only member of this complex endemic to solely volcanic regions, where it is found in wet lowland to premontane transitional forest on the eastern flanks of Costa Rica’s most active volcanoes. The ecology, distribution, and association with the Passiflora nitida complex is highlighted, as well as its relationship with the other species within Passiflora supersect. Laurifoliae found throughout Latin America.